(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The study aims to prepare complex exercises with tools that help in developing the level of achievement for the effectiveness of the long jump for young women and to identify the effect of exercises using the tools that help in developing the level of achievement in the pre and post test for the two groups for the effectiveness of the long jump for young women. It also tries to identify the effect of exercises using tools to help in developing the level of achievement in the post test and pre test for the two groups for the effectiveness of the long jump for young women.The researcher assumes that there are statistically significant differences between the pre and post tests of the effect of exercises with tools to help develop the level of achievement for the effectiveness of the long jump for young women, and there are statistically significant differences in the post test between the control and experimental research groups in developing the level of achievement for the effectiveness of the long jump for young women.The sample includes (4) female players. The players were chosen by the intentional method for their actual participation in the Kirkuk governorate clubs championship. They were divided equally into two equal groups, (2) players for each group (experimental and control). They were chosen randomly by drawing lots. (2) players were excluded for conducting pilot study on them. Thus, the percentage of the research sample became (80%) of the research community.